China-Pakistan economic relations: Lessons for Pakistan - Farrukh Nawaz Kayani; Mumtaz Ahmed; Tahir Ali Shah; Umar Nawaz Kayani (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2013)
The 60th anniversary of China-Pakistan relations was celebrated in 2011. Pakistan was the third non-communist and the first Muslim country to recognize China in 1950. The diplomatic relations between China and Pakistan were established in May 1951.The friendship between China and Pakistan is all weather and everlasting. The relationship is deeper than the oceans and higher than the mountains. The bolstering relations of China and Pakistan have become a model for a friendly co-existence of developing neighboring countries. China and Pakistan are enjoying strong bilateral cultural, economic and military relationships. Both of the countries are striving together for promoting peace, stability and economic prosperity in Asia. In the past, China-Pakistan ties were mainly of military and strategic importance. But now the economic relations of China-Pakistan are strengthening specially after the conclusion of Free Trade Agreement (FTA) in 2007. In this paper we would focus upon the economic relations of China and Pakistan. We also used the granger causality test to understand the relationship between Chinese Inward FDI and Economic Growth. We took the annual data from 1980 t0 2012. We found that growth in China caused inward FDI. Furthermore, it has been discussed that what Pakistan can learn from the miraculous economic progress and prosperity of China?
Keywords: 330; Chinese economy; Flying Geese model; foreign direct investment; free trade agreement; Pakistan's economy